Aerial Image Of Monitoring USM Campus Surrounding Area For Traffic Congestion Problem - Kholiq, Muhammad Iqmal Hakim Abd (Universiti Sains Malaysia, 2017)
Image processing technique is a very powerful tool to be used in object detection and tracking especially in traffic monitoring. There are plenty of ways to perform image processing technique depends on its specific focus of interest. The one that have been implemented in this project utilise Gaussian mixture model as the background segmentation and subtraction to obtain the foreground image that contains dynamic elements. The background elements contains static pixel which will be eliminated to observe the changes and predict its update. Gaussian mixture model is very robust for vehicle tracking and useful to observe the traffic condition on the road. Aerial imaging for foreground visual have been implemented to eliminate the overlapped information obtain by the ground detection. Foreground view for traffic monitoring also very convenient as it helps to eliminate the flaws that might been encounter for the ground view. The monitoring view is wider and much clearer as it overcome the vehicle overlapping problem for vehicles detection and tracking.